Ультразвуковая очистка оптико-механических систем - Tomal, V. S. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Ultrasonic cleaning of opto-mechanical systems (lenses in mounts) has been investigated, with attention to the influence of solution compositions and process parameters on cleaning quality. A solution is proposed that effectively removes contaminants without interacting with glass, mount materials, or functional coatings of opto-mechanical systems. A cleaning process using cyclohexane has been developed, ensuring high-quality treatment of optical components.